Repenser le temps et l'espace, du wampum au selfie - Vigneault, Louise (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
This article considers the way certain Indigenous artists are reviving conceptions of territory and history that are anchored in secular epistemologies and the construction of knowledge. Such conceptions provide a way for these artists to respond to colonial appropriation, reactivate interrupted dialogues, engender new forms of territorialization, and create places of commemoration and memory preservation. Similar to the historiographical deconstruction performed by thinkers and activists such as Vine Deloria Jr. and Taiaiake Alfred, these artists’ works offer a model of autonomy and environmental balance. While some are reviving mnemonic practices, such as the making of wampum, which traditionally preserve memories of alliances and conflicts, others have embraced Internet and selfie technologies as a means of creating new spaces for speech and recognition
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Mises en récit 2.0 de l'activisme autochtone. The Indigenous Archival Photo Project et What Brings Us Here - Pinto Ferretti, Alexia (L'agir en condition hyperconnectée. Art et images à l'oeuvre., 2020)
La question de la mémoire en condition hyperconnectée s’articule également dans le potentiel des réseaux sociaux pour la mise en visibilité de différents mouvements activistes autochtones au Canada. À travers deux études de cas, le projet The Indigenous Archival Photo Project par l’écrivain Paul Seesequasis (Cri des plaines) et la page Instagram What Brings Us Here mettant en vedette les groupes d’activistes à Winnipeg The Bear Clan et Drag the Red, ce chapitre réfléchit à la manière dont les créateur.rice.s autochtones utilisent les réseaux sociaux comme des vecteurs d’agentivité narrative témoignant de différents enjeux touchant les communautés. Ces projets doivent être considérés comme des opérateurs de changements, car ils participent à la valorisation des voix autochtones et à l’instauration de divers réseaux de solidarité. Par différentes stratégies conversationnelles en ligne, ces projets renouent ainsi avec le communautarisme propre aux médiums de communication traditionnels autochtones où le dialogue est primordial.
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Digital Identity: The Construction of Virtual Selfhood in the Indigenous Peoples' Movement - Niezen, Ronald (Comparative Studies in Society and History, 2005)
Inventions have their greatest impact when they go beyond their possible practical applications and act upon the imagination. When Martin Behaim invented the first globe in 1490, a functionally useless object consisting mostly of terra incognita, he was widely ridiculed; but somehow the ideas that his globe represented stuck, and within a few decades the basic validity of his construction was confirmed by the voyages of Columbus, Cabot, Vasco de Gama, Magellan, and others. Today, with efforts to situate the rapid growth of information and communication technologies (ICTs), especially the Internet, in the context of globalization, there is a similar division between those who dismiss it as being of no importance and those who see in it a looming (for good or ill) global revolution. But, as with Behaim's globe, the imaginary possibilities of these innovations are important in determining how and to what extent human existence is to be transformed by them
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

CyberPowWow: discours chronopolitiques autour des arts et muséographies numériques autochtones - L'Heureux, Isabelle (Université de Montréal, 2018)
Le collectif d'artistes Nation to Nation crée en 1996 CyberPowWow, une galerie d'art numérique autochtone en ligne. Entre 1997 et 2004, le projet voit quatre éditions se succéder et plus d'une vingtaine d'artistes y participer. CPW développe un modèle alternatif pour une production, une diffusion et une critique autodéterminée des arts numériques autochtones au Canada, ce qui lui confère une place importante dans la structuration de cette scène. Le présent mémoire vise à étudier la position de CPW - sa plateforme muséographique et ses œuvres - au sein d'un ensemble de discours chronopolitiques qui opèrent à l'intersection des arts, des technologies numériques et des identités autochtones
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

Indigenous Art: New Media and the Digital - Igloliorte, Heather; Nagam, Julie; Taunton, Carla (Public : art, culture, ideas, 0845-4450 ; volume 27, issue 54, 2016)
Indigenous Art New Media and the Digital convenes leading scholars, curators, and artists from the Indigenous territories in Canada, the United States of America, Australia, and Aotearoa (New Zealand). It brings forth urgent conversations about resistance to colonial modernism, and highlights the historic and ongoing use of technology by Indigenous communities and artists as vehicles of resilience and cultural continuity. This issue ignites productive dialogue around the definitions of new and digital media art and practice-based work within the framework of Indigenous art and theory
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Transference, Tradition, Technology: Native New Media Exploring Visual & Digital Culture - Townsend, Melanie A.; Hopkins, Candice (Walter Phillips Gallery Editions, 2005)
Transference, Tradition, Technology explores Canadian Aboriginal new media and references the work of artists within a political, cultural and aesthetic milieu. The book constructs a Native art history relating to these disciplines, one that is grounded in the philosophical and cosmological foundations of Aboriginal concepts of community and identity within the rigour of contemporary arts discourse. Approachable in nature but scholarly in content, this book is the first of its kind. A text book for students and teachers of Canadian Aboriginal history and visual and media art, and a source for writers, scholars and historians, Transference, Tradition, Technology is co-produced with the Art Gallery of Hamilton, Hamilton; and Indigenous Media Arts Group, Vancouver.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Coded Territories: Tracing Indigenous Pathways in New Media Art - Loft, Steve; Swanson, Kerry (University of Calgary Press, 2014)
This collection of essays provides a historical and contemporary context for Indigenous new media arts practice in Canada. The writers are established artists, scholars, and curators who cover thematic concepts and underlying approaches to new media from a distinctly Indigenous perspective. Through discourse and narrative analysis, the writers discuss a number of topics ranging from how Indigenous worldviews inform unique approaches to new media arts practice to their own work and specific contemporary works. Contributors include: Archer Pechawis, Jackson 2Bears, Jason Edward Lewis, Steven Foster, Candice Hopkins, and Cheryl L'Hirondelle.
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé